AYAT-AYAT REZEKI DALAM KARYA LUKIS KALIGRAFI KONTEMPORER - OCKY AFRIANTO, Drs. Syafei, M.Sg., Drs. Yusron Wikarya, M.Pd. (Universitas Negeri Padang, 2018)
This thesis aims to visualize the verses about blessings in form of contemporary callighraphy painting works as an effort to spread the verses of Quran especially about blessings which are closely related to daily life of mankind and to introduce the Islamic art work (callighraphy). The methods used in realization of ideas are preparation, elaboration, synthesis, concept realization, and finishing stage. There are ten contemporary callighraphy painting works which are made in form of acrylic on canvas. They are Al-Baqarah (2):172, Al-Baqarah (2):212, Hud (11):6, Ar-Ra’d (13):26, Al-Isra’ (17):31, Al-Hajj (22):50, Saba' (34):39, An-Najm (53):48, Al-Maidah (5):88, At-Talaq (65):2&3.Kata kunci: Rezeki, Ayat-Ayat Rezeki, Kaligrafi, Kaligrafi Kontemporer